Impact of Tigecycline Versus Other Antibiotics on the Fecal Metabolome and on Colonization Resistance to Clostridium difficile in Mice - Robin L.P. Jump; David Kraft; Kelly Hurless; Alex Polinkovsky; Curtis J. Donskey (Case Western Reserve University, 2017)
Background: The glycylcycline antibiotic tigecycline may have a relatively low propensity to promote Clostridium difficile infection in part because it causes less disruption of the indigenous intestinal microbiota than other broad-spectrum antibiotics.  We used a mouse model to compare the compare the effects of tigecycline versus other commonly used antibiotics on colonization resistance to C. difficile and on metabolic functions of the intestinal microbiota.   Methods: To assess in vivo colonization resistance to C. difficile, mice were challenged with oral C. difficile spores 1, 7, or 12 days after completion of 3 days of treatment with subcutaneous saline, tigecycline, ceftriaxone, piperacillin-tazobactam, or linezolid.  Levels of bacterial metabolites in fecal specimens of mice treated with the same antibiotics were analyzed using non-targeted metabolic profiling by gas chromatograph (GC)/mass spectrometry (MS) and ultra-high performance liquid chromatography-tandem MS (UPLC-MS/MS).  Results:  All of the antibiotics disrupted colonization resistance to C. difficile when challenge occurred 2 days after treatment.  Only piperacillin/tazobactam and ceftriaxone-treated mice had disturbed colonization resistance at 7 days after treatment.  All of the antibiotics altered fecal metabolites in comparison to controls, but tigecycline caused significantly less alteration than the other antibiotics, including less suppression of multiple amino acids, bile acids, and lipid metabolites.    Conclusions:  Tigecycline and linezolid caused transient disruption of colonization resistance to C. difficile, whereas ceftriaxone and piperacillin/tazobactam caused disruption that persisted for 7 days post-treatment.  Tigecycline caused less profound alteration of fecal bacterial metabolites than the other antibiotics, suggesting that the relatively short period of disruption of colonization resistance might be related in part to reduced alteration of the metabolic functions of the microbiota